Determining the rate of follow-up after hospital emergency department visits for dental conditions - Meyer B; Adkins E; Finnerty NM; Robinson FG (Dove Medical Press, 2016)
Beau Meyer,1,2 Eric Adkins,3,4 Nathan M Finnerty,4 Fonda G Robinson5 1Division of Pediatric Dentistry, College of Dentistry, The Ohio State University, Columbus, OH, 2Department of Pediatric Dentistry, School of Dentistry, University of North Carolina at Chapel Hill, Chapel Hill, NC, 3The Ohio State University Wexner Medical Center Emergency Department, 4Department of Emergency Medicine, College of Medicine, 5Clinic Administration and Patient Care, College of Dentistry, The Ohio State University, Columbus, OH, USA Background: Emergency department (ED) visits for dental reasons continue to impact EDs nationwide. This investigation determined the rate of follow-up in an emergency dental clinic (EDC) after hospital ED visits for nontraumatic dental conditions. Methods: This prospective investigation reports the number of patients who presented to an ED for nontraumatic dental conditions and the rate of follow-up at an EDC. Upon ED discharge, patients were provided instructions to follow-up for low-cost care at the EDC. Telephone contact was attempted following failed referrals. Descriptive statistics were reported for comparing referral sources and demographic trends. Results: Two hundred and forty-seven referrals were made and 31% followed up for definitive treatment at the EDC. More referrals were made on weekends than on weekdays. Failed referrals were unreachable by telephone in 75% of cases. Tooth extraction was the most common treatment rendered in the EDC. Of the ED patients who accessed EDC care, 14% became comprehensive patients in the EDC's regular dental clinic. Conclusion: Less than one-third of ED referrals to the EDC followed up for definitive care when provided an opportunity to do so, and 75% of referrals were unreachable by telephone in the week following the ED dental visit. Keywords: emergencies, dental health services, health services accessibility, access to care, dental emergency treatment